Equivariance, Variational Principles, and the Feynman Integral - Svetlichny, G. (Symmetry, Integrability and Geometry: Methods and Applications, 2008)
We argue that the variational calculus leading to Euler's equations and Noether's theorem can be replaced by equivariance and invariance conditions avoiding the action integral. We also speculate about the origin of Lagrangian theories in physics and their connection to Feynman's integral.